Developing a SmartRail Security System with YOLO and OpenCV - Jyothis, Siva; Nair, Anand S; VR, Kirandas; M, Rohith; Visakh, Divya (Journal of Ubiquitous Computing and Communication Technologies, 2024)
SmartRail Security System is an innovative research designed to significantly enhance security and safety measures within the station. The primary objective of this research is to implement advanced surveillance technology, revolutionizing the security infrastructure of the railway station and ultimately creating a smarter and more efficient approach to protecting the station environment completely. The SmartRail security system prioritizes key features aimed at enhancing rail station security System. It incorporates state-of-the-art missing person tracking capabilities that allow rapid identification and monitoring of individuals with previous missing records within the station premises. The system's goal is to provide real-time tracking and analysis, ensuring proactive measures are taken to prevent and respond swiftly to security threats. The purpose of the SmartRail security system is to combat illegal intrusion inside the restricted area of the railway station. The aim of this system is to create a strong monitoring system by introducing smart monitoring tools. This will strengthen the defenses against unauthorized access and bolster the overall security situation of the station comprehensively. SmartRail security systems go beyond mere surveillance; they promise to redefine safety standards within the station. This smart and efficient approach is deemed essential to ensure the security of staff and the entire station environment.
Keywords: Smartrail Security System; Advanced Surveillance Technologies; Missing Tracking Capabilities. Unauthorized Access